2020
DOI: 10.1002/ange.202011886
|View full text |Cite
|
Sign up to set email alerts
|

Azadiphosphaindan‐1,3‐diyle: Eine Gruppe von resonanzstabilisierten Biradikalen

Abstract: Die Umsetzung von 1,2-Bis(dichlorphosphanyl)benzol mit sterisch anspruchsvollen primären Aminen führte zur Bildung von 1,3-Dichlor-2-aza-1,3-diphosphaindanen des Typs C 6 H 4 (m-PCl) 2 N-R. Reduktion derselbigen ergab die entsprechenden 2-Aza-1,3-diphosphaindan-1,3-diyle (1), die als phosphorzentrierte Singulett-Biradikal(oid)e beschrieben werden kçnnen. Ihre Stabilität hängt von der Grçße des Substituenten R ab: Während Derivate mit R = Dmp (2,6-Dimethylphenyl) oder Ter (2,6-Dimesitylphenyl) oligomerisierten,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…and NICS(1) zz values (−30.2/−28.3 ppm) of 5H are in the range of other related aromatic ring systems, such as indole and azadi‐phosphaindane‐1,3‐diyl, indicating that compound 5H possesses significant aromatic character. In contrast, values for 2H (which was previously investigated by us) differ notably and are significantly smaller (3.5 nAT −1 , −7.2 ppm), implying that 2H is best regarded as a non‐aromatic compound [69,70] . In Figure 8 the current density susceptibility of the model system 5H is depicted as streamline representation.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…and NICS(1) zz values (−30.2/−28.3 ppm) of 5H are in the range of other related aromatic ring systems, such as indole and azadi‐phosphaindane‐1,3‐diyl, indicating that compound 5H possesses significant aromatic character. In contrast, values for 2H (which was previously investigated by us) differ notably and are significantly smaller (3.5 nAT −1 , −7.2 ppm), implying that 2H is best regarded as a non‐aromatic compound [69,70] . In Figure 8 the current density susceptibility of the model system 5H is depicted as streamline representation.…”
Section: Resultsmentioning
confidence: 80%
“…Since we assumed that one of the driving forces for the formation of azaphosphole 5 is its larger aromaticity as opposed to the five‐membered biradical 2 , NICS(1) zz values (Nucleus‐Independent Chemical Shifts) and magnetically induced ring current susceptibilities, which represent common parameters to describe aromaticity, were calculated for the model compounds 2H and 5H (Figure 8, Table 1). [70–77] The net induced ring current (13.2/12.2 nAT −1 for 6‐ and 5‐membered rings, resp.) and NICS(1) zz values (−30.2/−28.3 ppm) of 5H are in the range of other related aromatic ring systems, such as indole and azadi‐phosphaindane‐1,3‐diyl, indicating that compound 5H possesses significant aromatic character.…”
Section: Resultsmentioning
confidence: 99%
“…It has already been shown that the base‐induced reaction of 2 with primary amines can form fused ring systems such as 11R and the subsequent reduction can lead to biradicals [11] . To demonstrate an exemplary application of the new chlorophosphanes, compound 6 was treated with one equivalent of Ter‐NH 2 (Ter=2,6‐dimesitylphenyl) in the presence of the base NEt 3 in CH 2 Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Here, the para , [9] meta , [10] as well as the ortho substituted [10] bis(dichlorophosphino)benzene has been described. For our own research, the ortho ‐isomer 1,2‐bis(dichlorophosphino)benzene ( 2 ) is of special interest, since it can be used to build five‐membered rings in the reaction with primary amines [11] . For 2 , a variety of three‐step synthesis routes were described, which are summarized in Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation